A filosofia da ciência de John Dewey e a dicotomia fato/valor : ciência e ética - Acevedo, Natanael David (2017)
The scope of this dissertation is to analyze John Dewey's proposal for a philosophy of science. Notably, we show how the development of his theses in this direction was a counterpoint to the fact/value dichotomy. Early 20th century philosophy of science many times postulated that knowledge and scientific research should be reserved to the study of facts, that is, that which is real and true about the world. This scientific endeavor kept value knowledge and concepts apart from the scientist's daily concerns. Thus, moral and ethics, along with other investigative means under the value terminology, would not be capable of conceiving any sort of truth about the world, only subjective conceptions, related to individual cases, from which objective concepts applicable to all cases is not possible. Given this situation, our intention here is to investigate which features of Dewey's work allow for an interpretation of philosophy of science that does not embrace a dichotomy, particularly one who separates facts from values in science activities. To do so, we began with a general overview concerning the fact/value dichotomy in philosophy of science. First, we make use of some of Dewey's writings in which he lays out his rejection of dichotomist postulates, followed by a perspective of this aspect through a contemporary criticism. After this overview, we present some philosophical bases for Dewey's pragmatism thru the ideas of Peirce and James, so that the reader might become acquainted with its concepts. Following, we contemplate Dewey's proposal for philosophy of science by means of the concepts of investigation and situation, which will allow us to hold our initial arguments in this research. Finally, we conclude that Dewey's philosophy does not partake in the dichotomist theses, but stands apart from them so to regard values to be present in every aspect of scientific investigation, making it so that ethical consequences of such endeavor become a responsibility of its practitioners.